(3TQM GdebGeGJ GdMQjQjs - (3CHi YHO Gddg MLI GdOjf eMeO Hf YHO Gddg CHi eMeO Hf eMeO Hf XaQ GdUbdj Gdecjs; (3GdMQjQj,J (B516 (3g` s ((3eMeO Hf CHj GdeLO Hf YHOGdZaGQ GdJejei GdSgQhQOi s)
(3ChdgG (B:s
(3hHYO aEfc SCdJfi CjgG GdCN GdQTjO hGdUGMH GdSOjO TQM eG JTJed Ydjg GdebGeGJ hJMJhjg ef GdETJbGbGJ GddZhjI s
(3BNQgG (B:s
(3hajeG bOeJg ef GdZOQ Edi Ggd GdHdGZI hGdHQGYI ai GdJLGhR hGdYah Yf SbWGJ GdZdW hGdfSjGf hGdSgh hGdMeO ddg s
(3GdTQM GdeWhd (B- (3GdcHjQs
(3ChdgG agQS HNW eZGjQs
(3HHYV ChQGbgG GVWQGH ai GdJQJjHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs